Cyclic testing of a steel-tube-enabled emulative precast column-to-column connection - Ming-Ming Ji; Ming-Ming Ji; Wei Chen; Shi Zeng; Yan Xiong; Xin-Yu Zhao (Frontiers in Materials)
Precast systems are increasingly favored in modern construction to meet the growing demands for faster project delivery, cost control, and enhanced quality assurance. Yet, the feasibility of connections between precast elements remains a crucial factor affecting the overall structural performance of these systems. Considering the versatility and dimensional consistency of structural steel sections, this study introduces an emulative column-to-column hybrid connection achieved by using welding-spliced steel tubes, with a view to improving assembly efficiency and on-site quality control. Reversed cyclic loading tests were conducted on five near full-scale column specimens to assess the seismic performance of the proposed connection. Results indicated that this connection method could provide seismic performance comparable to that of the traditional cast-in-place counterpart. Nevertheless, the anchorage of the column longitudinal rebars played a critical role, as inadequate anchorages led to significant reductions in the columns’ lateral capacity. For this reason, increasing the tube thickness was shown to be insufficient as a substitute for proper anchorage detailing. Moreover, it was found that the incorporation of the welded steel tubes shifted the plastic hinge region upward, resulting in a more extended damage zone—a consequence of the localized stiffening effect. Finally, existing equations and methods are employed to evaluate the lateral strength, load-displacement response, and plastic hinge length of the tested specimens.